Experimental techniques used in the high temperature heat-treatment of some tungsten-thoria alloys - Younger, A. (College of Aeronautics, 1964)
The high temperature apparatus developed in the Department of Materials for the torsional creep testing of graphite at temperatures up to 3000 oC has been utilised to heat-treat tungsten-thoria alloys at temperatures up to 2500 oC. Modifications to the torsional loading system have enabled some of these heat-treatments to be carried out under an applied stress.